Towards a Maturity Model for Accounting and Financial Sustainability in Indonesian MSMEs: Insights from a Systematic Literature Review - Yumniati Agustina; Yvonne Augustine (Universitas Pasundan, 2024)
This research aims to gather insights and synthesize information by conducting a methodical review of existing literature to identify dimensions and aspects for creating a maturity model for evaluating the preparedness of Micro, Small, and Medium Enterprises in Indonesia regarding their accounting and financial sustainability. Employing the PRISMA method, the study reviewed papers in Scopus and Google Scholar from 2000 to 2021, uncovering 10 dimensions and 20 measurement aspects crucial for assessing MSMEs’ readiness in this area. The research contributes to existing literature and guides future accounting and finance research, with a specific focus on the sustainability of Indonesian MSMEs. Notably, there is a lack of research on the sustainability of MSMEs within accounting and finance. The dimensions and aspects identified will inform the development of a tailored maturity model to address accounting and financial sustainability within Indonesian MSMEs, offering insights to economic policymakers and stakeholders to advance MSMEs in alignment with environmental, economic, social, and governance principles. The literature search was conducted using only two databases and a relatively short publication timeframe.